Capacity Building on the Construction of Biopores and Infiltration Wells for Flood Mitigation in Songgon Sub-district, Banyuwangi Regency - M Rizqon Al Musafiri; Nawal Ika Susanti (CENDEKIA: Jurnal Pengabdian Masyarakat, 2025)
Songgon Sub-district in Banyuwangi frequently experiences flooding due to high rainfall intensity and insufficient drainage infrastructure. Community-based solutions are needed to address this recurring problem in a sustainable manner.  This study employed the Asset-Based Community Development (ABCD) approach to empower the local community in constructing biopores and infiltration wells as flood mitigation measures. The stages included asset identification (Discovery), formulation of shared goals (Dream), program design (Design), resource organization (Define), and implementation with sustainability planning (Destiny). Community training and facilitation were central components of the intervention. The ABCD approach effectively increased community engagement and participation. Several biopores and infiltration wells were successfully installed in targeted areas. These interventions contributed to improved groundwater recharge and reduced surface water runoff. Success factors included active community involvement, collaboration with village authorities, and the use of local resources. ABCD-based facilitation in constructing biopores and infiltration wells provides a participatory and sustainable strategy for flood mitigation in Songgon Sub-district. The approach demonstrates the importance of local empowerment and resource mobilization in addressing environmental challenges.